Wacana Teologis Kontra Demokrasi Pancasila: Analisis Sosio-Pragmatis Terhadap Al-Qur’an Tarjamah Tafsiriyah Muhammad Thalib - Sobirin, Mohamad (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2020)
The Al-Qur’an Tarjamah Tafsiriyah, which is initiated by Muhammad Talib as a correction to the Al-Qur’an Tarjamah Kementerian Agama which was considered as a source of radicalization, has found its paradox in the Qur’anic translation regarding the relation between Islam and state. This paper intends to answer two questions: what is the strategy of Muhammad Thalib in translating verses containing the keywords of taghut, tahkim, uli al-amr and awliya' and how relevant is the translation to the context of Indonesian Pancasila and democracy? By using socio-pragmatic theory, this paper argues that the ideology of counter-Pancasila democracy has lied in the Al-Qur’an Tarjamah Tafsiriyah. It obviously appears in the texts of translation that Thalib attempt to fight for the formalization of Sharia as a state positive law. Muhammad Thalib, for example, more often interpreted the word taghut in the Qur’an as heretical rules. These rules are contextually interpreted as thoughts, concepts, and ideologies that lead people to go astray from the way of God, including democracy, pluralism, secularism, liberalism, and Pancasila.